Śākyabhikṣu of Nepal Maṇḍala: Its Antiquity and Correlation - Shakya, Sanjay (Journal of Buddhist Studies (T.U.), 2025)
In this paper, the Buddhist community of “Śākyabhikṣu” widely known for their ordination in Mahāyāna/Vajrayāna tradition in Nepal Maṇḍala is discussed. It is with certainty that, “Śākyabhikṣu” is not a term only constrained to the Newaḥ tradition in Nepal but also its connection to ancient historical records from Indian inscriptions mostly worth of mention is Ajantā caves. The community of “Śākyabhikṣu” is well displayed and understood for their obligations from there. Whereas, in the Nepalese perspective, it is most likely a title borne by the Śākyas as an honorary depiction. It must not be limited to what was thought in surficial understanding but needs to interpret and explore what might come up with ancient Buddhist tradition we followed in Nepal from its inception. Some inscriptional tallies and correlations with Indian inscriptions and traditions are made with Nepalese tradition in this paper. The explanatory approach of the word “Śākyabhikṣu” and its etymology along with some comparative descriptions in India and Nepal is given emphasis. However, the bigger portion of the interpretation relies on the current practices of the sangha members of Buddhist Mahāvihāras who called themselves “Śākyabhikṣu” or terminologies well connected with “Śākyas”. So, the paper follows descriptive yet somewhat analytic methodologies on cultural observation with historical blending for the interpretation of “Śākyabhikṣu’s” legacy.